Adoption for adaptation: A theory-based approach for monitoring a complex policy initiative. (April 2019) - McConnell, Jesse
Highlights: Complex policy initiatives present challenges for designing monitoring frameworks to adequately capture their progress and results. A theory-based approach to designing a monitoring framework presents viable options to capture a diverse programme portfolio and challenging implementation environment. Evaluative indicators are offered as a way of systematically incorporating context monitoring into a framework to ensure contextual dynamics and changes are captured and incorporated into programme decisions. Categorical indicators provide a flexible arena to capture diverse programme support across multiple sectors and locations. Ensuring that the causal pathway of an influencing intervention is reflected in a monitoring framework in the form of output adoption and implementation offers a framework through which to infer a programme's causal effects. Abstract: This paper explores some of the challenges involved in designing a monitoring framework for a complex policy initiative designed to support climate change adaptation in a highly varied and dynamic implementation environment. It looks specifically at the UK's Department for International Development (DFID) initiative called Action on Climate Today, a five-year programme that aims to support the mainstreaming of climate change adaptation into policy systems in five countries and ten locations in South Asia. This paper presents a theory-based approach to designing a monitoring system for the ACT programme that seeks to account for the programme's design and implementation complexities. It does so by providing an example for monitoring the causal processes and mechanisms that underpin the programme's theory of change. The paper highlights a systematic approach to context monitoring through periodic context assessments and evaluative indicators; the use of categorical indicators to capture a diverse portfolio of support; and a flexible results framework structured around the adoption and implementation of programme outputs into the targeted policy systems.